Single trans‐septal access technique for left atrial intracardiac echocardiography to guide left atrial appendage closure. Issue 2 (24th August 2017) - Aguirre, Daniel; Pincetti, Christian; Perez, Luis; Deck, Carlos; Alfaro, Mario; Vergara, Maria Jesus; Maluenda, Gabriel
Abstract: Objective: This registry aimed to describe the safety and feasibility of a single trans‐septal (TS) access technique for left intracardiac echocardiography (ICE) guidance of left‐atrial appendage (LAA) closure procedure. Background: LAA closure is currently accepted as an alternative to oral anticoagulation (OAC) in patients with non‐valvular atrial fibrillation (NVAF) who are at high‐risk for bleeding. Currently, LAA closure procedure is typically performed under trans‐esophageal echocardiogram (TEE) guidance. Although, ICE has the advantage of not requiring profound sedation/anesthesia, ICE‐LAA imaging quality is often limited from the right atrium requiring double TS access. Methods: Twenty‐two patients with NVAF underwent LAA closure using the Amplatzer Amulet™ device (St Jude Medical) under ICE guidance from the left atrium. The ICE AcuNav catheter (Biosense Webster) and the Amulet delivery sheath were advanced into the LA through single TS puncture technique. Results: The population was predominately male (59.1%) with a mean age of 74 ± 9.3 years, at high‐risk for stroke (mean CHADS2 score of 3.8 ± 1.1) and bleeding (mean HAS BLED score of 3.5 ± 1.3). The Amplatzer Amulet TM device was successfully implanted in all patients. No procedural related complications including device embolization were noted. No major cardiovascular events occurred and all patients were discharged alive. At 30‐day follow‐up all patients remained alive, free of ischemic stroke and with no residual leak or device thrombus on TEE. Conclusions: This initial experience suggests that LAA occlusion with the Amplatzer Amulet device using ICE guidance from the left atrium via a single trans‐septal technique is feasible and safe.